C.I.D.N.P. enhancement of both organometallic and organic compounds in the thermal reaction of [Ti(CH2Ph)Cl(c-C5H 5)2] with CCl4 - KELLY, JOHN MOFFAT (My University, 1982)
The thermal reaction of [Ti(CH,Ph)CI(q-C5H5)2] with CCI4 in r2HSb] enzene solution gives enhanced signals for both the starting titanium compound and product PhCH2CCI3, but not in titanocene dichloride or bibenzyl which are also produced; a mechanism accounting for these observations is proposed.
PUBLISHED
Keywords: thermal reaction; thermal reaction